Assessment of Process, Parameters, Residual Stress Mitigation, Post Treatments and Finite Element Analysis Simulations of Wire Arc Additive Manufacturing Technique - Barath Kumar, M. D.; Manikandan, M. (Metals and materials international, 2022)
Wire arc additive manufacturing (WAAM) technique became an emerging manufacturing technology because of its cost-effective in creating large-scale metal parts with moderately high deposition rates. Mainly, WAAM works through the utilization of heat source as an electric arc by melting the metal wire to build the three-dimensional metal parts in a layer-by-layer approach, which may significantly minimize the fabrication costs compared to powder and other additive manufacturing techniques such as laser and electron beam, similarly. This article reviews WAAM processes and methods and gives an exhaustive overview of the residual stresses, microstructures, and material properties of the as-fabricated and post-fabrication treated WAAM components. The typical defects during the fabrication of metal components by the WAAM process are residual stresses, deformity, porosity, and cracking. And also, methods on controlling residual stresses, improving material properties, and effects of post-processing treatments to enhance the part quality fabricated by using the WAAM process are recommended in this review. Finally, the measurement methods of residual stresses in the metal parts and FEA simulations in the WAAM are discussed. FEA simulations provide better insights on moving heat source model, temperature distributions, and residual stresses in the WAAM process. This article concludes that selecting process parameters affects the quality WAAM component during the deposition process. And also, approaches to improving the part quality are proposed. The materials fabrication issues in the WAAM processes were outlined, and the advanced WAMM processes were suggested to obtain high quality and defect-free WAAM parts. Graphic Abstract